2017
DOI: 10.1088/1751-8121/aa5301
|View full text |Cite
|
Sign up to set email alerts
|

Positive tensor products of maps andn-tensor-stable positive qubit maps

Abstract: We analyze positivity of a tensor product of two linear qubit maps, Φ1 ⊗ Φ2. Positivity of maps Φ1 and Φ2 is a necessary but not a sufficient condition for positivity of Φ1 ⊗ Φ2. We find a nontrivial sufficient condition for positivity of the tensor product map beyond the cases when both Φ1 and Φ2 are completely positive or completely co-positive. We find necessary and (separately) sufficient conditions for n-tensor-stable positive qubit maps, i.e. such qubit maps Φ that Φ ⊗n is positive. Particular cases of 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…In this subsection we consider unital qubit maps     U  ( ) ( ) : Consider a local unital map acting on two qubits, ¡ Ä ¡¢. General properties of such maps are reviewed in [15,39].…”
Section: Local Unital Qubit Maps and Channelsmentioning
confidence: 99%
“…In this subsection we consider unital qubit maps     U  ( ) ( ) : Consider a local unital map acting on two qubits, ¡ Ä ¡¢. General properties of such maps are reviewed in [15,39].…”
Section: Local Unital Qubit Maps and Channelsmentioning
confidence: 99%
“…Such a map is easily seen to be decomposable, and reversing the scaling operation shows that the original map is decomposable as well. Recently, S. Fillipov and K. Magadov [14] analyzed when tensor squares of qubit maps are positive. Specifically, they showed that for the Pauli diagonal map with |µ = (1, x, y, z) T ∈ R 4 its tensor square Π µ ⊗ Π µ is positive if and only if the following inequalities hold:…”
Section: Motivation and Summary Of Main Resultsmentioning
confidence: 99%
“…Further, a result in [ 25 ] ensures that, for trace preserving qubit maps , the Positivity of the tensor product maps, , on two qubits is equivalent to the Complete Positivity of the squares, , of the 1-qubit maps. Since from (27) it follows that acts as by changing α into , is Positive for .…”
Section: Open Quantum Dynamicsmentioning
confidence: 99%